Muhammad Ibn Ibrahim al Jumayh : Amir al Washim fi al dawlat al su'udiyyah al ula 1218-1229 H. Hayatuhu, A'maluhu, Dhariyatuhu - Yusuf Ibn Abdul Aziz al Muhana (Maktabat al Malik Fahd al Wataniyyah)
ws1/ws.c.1